Ønlev-kvinden - en højstatus kvindegrav med et kirurgisk redskab fra yngre romersk jernalder (225-250 e.Kr.) - Riis, Katrine Moberg; Frölich, Annette (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
During 2017 – 2019, the Museum Sønderjylland – Arkæologi excavated a site (31.710 m2) located at Kassø (Rødekro) in advance of building activities. A female grave, which promised to be quite interesting due to her grave goods, was found here. The deceased was buried with grave goods consisting of pottery, glass and amber beads, copper alloy brooches, a silver brooch, a knife in a special scabbard, and an artefact which is interpreted as a surgical instrument. Analyses and comparisons of grave goods indicate the social status of the female, probably also of her origin, as well as the date of the grave to C1 b (225 – 250 AD). The surgical instrument is analysed, interpreted, and discussed in detail. It is argued that the Ønlev- grave is the only known Iron Age grave, found outside the Roman Empire, which we may assume to be the grave of a physician dating to the period 225 – 250 AD.